2012
DOI: 10.1007/s10948-012-1539-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ni Substitution in Bi-2212 Superconductors

Abstract: In this study the samples were synthesized from a 2234 stoichiometric composition in order to obtain a large amount of pure 2212-BSCCO. The effects of Ni substitution on the properties of Bi-based Bi 2−x Ni x Sr 2 Ca 1 Cu 2 O y superconductor with x = 0, 0.05, 0.1 and 0.2 were investigated by means of X-ray analysis (XRD), DC electrical resistivity and magnetic-hysteresis loop measurements. It has been found that the T c (onset) transition temperature does not change independently of Ni content. In addition, J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…Moreover, n is related to the number of CuO 2 layers in the crystal structure, producing the well-known Bi-2201, 2212 and 2223, respectively, with 20, 85, and 110 K critical temperatures for each one [2][3][4]. Since the discovery of high-Tc superconductivity in the BSCCO system [1], intense studies have been performed [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] in order to improve its critical temperature (Tc), critical current density (Jc), and better understand the structural properties of the system. One of the useful methods, in this regard, is the substitution of rare-earths elements at different cationic sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, n is related to the number of CuO 2 layers in the crystal structure, producing the well-known Bi-2201, 2212 and 2223, respectively, with 20, 85, and 110 K critical temperatures for each one [2][3][4]. Since the discovery of high-Tc superconductivity in the BSCCO system [1], intense studies have been performed [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] in order to improve its critical temperature (Tc), critical current density (Jc), and better understand the structural properties of the system. One of the useful methods, in this regard, is the substitution of rare-earths elements at different cationic sites.…”
Section: Introductionmentioning
confidence: 99%
“…The texturing methods can be roughly divided into solid state methods, where the sample is maintained as a solid [27,28] and those where the sample is totally molten (directional solidification techniques). Among these last methods, the Laser Floating Zone (LFZ) one has been demonstrated to be an effective technique to produce a good grain orientation not only in Bi-2223 [29,30] and Bi-2212 [22,31] superconductors, but also in other anisotropic systems [32]. This method produces very high thermal gradients in the solidification front, producing a preferential alignment of grains with their c-axis perpendicular to the growth direction [33], maximizing the transport properties in the direction parallel to the growth axis.…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of high-T c superconductivity in the BSCCO system [1], intense studies have been performed on high-T c BSCCO system in order to improve its critical temperature (T c ), critical current density (Jc), and better understand the structural, physical and magnetic properties of the superconducting phase [2][3][4][5][6][7][8][9][10][11][12][13][14]. These works have shown that the addition and/or substitution of rare-earth elements in the Ca/Cu site plays a critical role, not only leading to important changes in charge carrier concentration but also releasing the restriction of spin alignment due to the spin lattice interactions [15].…”
Section: Introductionmentioning
confidence: 99%
“…6. From this figure, it is obvious that J C values are very high and decrease with increasing the external magnetic applied field due to the weak links between grains [39]. However, these magnetically obtained critical current densities are higher than the transport critical current densities where the weak grain links and the grains orientation are also taken into account.…”
Section: Resultsmentioning
confidence: 92%